A proteomics approach to investigate the process of Zn hyperaccumulation in Noccaea caerulescens (J & C. Presl) F.K. Meyer. (26th October 2012) - Schneider, Thomas; Persson, Daniel Pergament; Husted, Søren; Schellenberg, Maja; Gehrig, Peter; Lee, Youngsook; Martinoia, Enrico; Schjoerring, Jan K.; Meyer, Stefan
Summary: Zinc (Zn) is an essential trace element in all living organisms, but is toxic in excess. Several plant species are able to accumulate Zn at extraordinarily high concentrations in the leaf epidermis without showing any toxicity symptoms. However, the molecular mechanisms of this phenomenon are still poorly understood. A state‐of‐the‐art quantitative 2D liquid chromatography/tandem mass spectrometry (2D‐LC‐MS/MS) proteomics approach was used to investigate the abundance of proteins involved in Zn hyperaccumulation in leaf epidermal and mesophyll tissues of Noccaea caerulescens . Furthermore, the Zn speciation in planta was analyzed by a size‐exclusion chromatography/inductively coupled plasma mass spectrometer (SEC‐ICP‐MS) method, in order to identify the Zn‐binding ligands and mechanisms responsible for Zn hyperaccumulation. Epidermal cells have an increased capability to cope with the oxidative stress that results from excess Zn, as indicated by a higher abundance of glutathione S ‐transferase proteins. A Zn importer of the ZIP family was more abundant in the epidermal tissue than in the mesophyll tissue, but the vacuolar Zn transporter MTP1 was equally distributed. Almost all of the Zn located in the mesophyll was stored as Zn–nicotianamine complexes. In contrast, a much lower proportion of the Zn was found as Zn–nicotianamine complexes in the epidermis. However, these cells have higher concentrations of malate and citrate, and these organic acids are probably responsible for complexation of most epidermal Zn. Here we provide evidence for a cell type‐specific adaptation to excess Zn conditions and an increased ability to transport Zn into the epidermal vacuoles.